Translational Implications for Off-the-shelf Immune Cells Expressing Chimeric Antigen Receptors - Torikai, Hiroki (Mol Ther, 2016)
Chimeric antigen receptor (CAR) endows specificity to T-cells independent of human leukocyte antigen (HLA). This enables one immunoreceptor to directly target the same surface antigen on different subsets of tumor cells from multiple HLA-disparate recipients. Most approaches manufacture individualized CAR(+)T-cells from the recipient or HLA-compatible donor, which are revealing promising clinical results. This is the impetus to broaden the number of patients eligible to benefit from adoptive immunotherapy such as to infuse third-party donor derived CAR(+)T-cells. This will overcome issues associated with (i) time to manufacture T-cells, (ii) cost to generate one product for one patient, (iii) inability to generate a product from lymphopenic patients or patient's immune cells fail to complete the manufacturing process, and (iv) heterogeneity of T-cell products produced for or from individual recipients. Establishing a biobank of allogeneic genetically modified immune cells from healthy third-party donors, which are cryopreserved and validated in advance of administration, will facilitate the centralizing manufacturing and widespread distribution of CAR(+)T-cells to multiple points-of-care in a timely manner. To achieve this, it is necessary to engineer an effective strategy to avoid deleterious allogeneic immune responses leading to toxicity and rejection. We review the strategies to establish “off-the-shelf” donor-derived biobanks for human application of CAR(+)T-cells as a drug.